Are fertilizer subsidies in Malawi value for money? - De Weerdt, Joachim; Duchoslav, Jan (International Food Policy Research Institute, 2022)
It is easy enough to calculate how much the Government of Malawi spends on subsidizing chemical fertilizer. Last year, for example, this was MWK 120 billion (about US$ 150 million) taking up over 50% of the agricultural budget. It is much harder, however, to calculate the benefits that these subsidies bring about and how they stack up against the costs. In this policy note, we combine multiple methods and sources of data to narrow down the range of possible benefit estimates, compare it to the cost of subsidies, and propose changes to current policies to make fertilizer subsidies more efficient and affordable.